Between Playfulness, Trauma, and Autofiction: Postmemories of Childhood in Dictatorial Argentina and Chile - Mendes, Rafael (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2022)
This dissertation explores the dynamic between postmemory, trauma, playfulness, and autofiction in The Rabbit House by Argentinian writer Laura Alcoba and Space Invaders by Chilean writer Nona Fernández. Since the early 2000s, artists whose childhood was marked by the dictatorship have been exploring their memories of the period within a broader national effort to create a new master narrative of the past. These narratives are based on postmemory, a system of transmission of traumatic experiences, and fill the gaps of memory with autofiction, a hybrid literary genre that exists in the liminal space between fiction and autobiography. The dissertation will explore trauma at the individual and national level, describing how the threat of violence disturbed childhood but will do so by seeing trauma not as a place of suffering and victimhood but of agency and creative potential. To achieve these overarching goals, this dissertation is divided into three chapters. The first chapter shows how trauma, postmemory, and autofiction will be employed and assess the predominant theories of each field of study. The second chapter analyses the novel Space Invaders, focusing on the convoluted relation between children and the adult world and children’s political activism going from playful activism to traditional modes of agency. It also explores Fernández’s multi-voiced narrator as a collective effort to remember the past. The third chapter analyses the novel The Rabbit House, exploring the life of a child living underground and how violence traumatised and pervaded the narrator’s vocabulary. Furthermore, it probes the conflicting relation between family, the child, and adult institutions and delves into the process of working through trauma at the national and individual levels. The conclusion presents the dissertation’s findings and proposes themes and areas for future research
Keywords: Comparative Literature